Layout planning for food manufacturing in industry 4.0. A literature review - Noriega Araníbar, María Teresa (2022)
The present research reports the analysis of studies published in the Scopus and Google Scholar databases between the years 2011 and 2020. The objective is to examine what new ways of planning facility design have been developed for food manufacturing for the fourth industrial generation. The theoretical justification for this research is that it is conducted for the purpose of confronting the theory of layout planning using the SLP with other existing ones. From a documentary, exploratory and systematized design, the results reveal that systematic layout planning (SLP) is maintained and that its application allows facilities for maintenance, better inventory management, cost reduction and sustainability in the food industry.